2020
DOI: 10.18502/ijrm.v13i5.7154
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes among pregnant women with different polycystic ovary syndrome phenotypes: A cross-sectional study

Abstract: Background: Pregnancy is a process associated with various metabolic and hormonal changes, and polycystic ovary syndrome (PCOS) can affect this process. Objective: This study aimed to evaluate and compare the maternal and neonatal outcomes among pregnant women with different polycystic ovary syndrome phenotypes. Materials and Methods: In this cross-sectional study, 200 pregnant women with PCOS according to the 2003 ESHRE/ASRM criteria were categorized into four phenotype groups (A-D). The maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) is a common endocrinopathy with complex pathophysiology that can result in anovulatory infertility in women ( Tanbo et al, 2018 ; Khan et al, 2019 ; Dehghani Firoozabadi et al, 2020 ). In addition to infertility, PCOS can give rise to hyperandrogenism, oligomenorrhea, hyperinsulinemia, chronic anovulation, and an increased risk of metabolic disorders such as type 2 diabetes and cardiovascular disease ( Louwers and Laven, 2020 ; Osibogun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a common endocrinopathy with complex pathophysiology that can result in anovulatory infertility in women ( Tanbo et al, 2018 ; Khan et al, 2019 ; Dehghani Firoozabadi et al, 2020 ). In addition to infertility, PCOS can give rise to hyperandrogenism, oligomenorrhea, hyperinsulinemia, chronic anovulation, and an increased risk of metabolic disorders such as type 2 diabetes and cardiovascular disease ( Louwers and Laven, 2020 ; Osibogun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…ICU admissions differed among the three PCOS groups; however, after correction, this was not statistically significant [ 44 ]. Among the four phenotypes of PCOS studied, no statistically significant differences were found in the incidence of neonatal birth weight, neonatal icterus, NICU admission, or neonatal death [ 45 ]. While a good amount of studies found additional risks, several studies found no difference in Apgar, birth weight, and incidence of hypoglycemia, which was also seen in comparing fertilization methods [ 37 , 39 , 43 , 44 , 46 ].…”
Section: Reviewmentioning
confidence: 99%
“…PCOS consists of four phenotypes A-D, but in general, it has been observed that pregnant women with PCOS consisting of hyperandrogenism and oligomenorrhea, such as A and B, were at an increased risk of developing GDM [ 47 , 48 ]. Conclusions of which phenotype was more likely to develop GDM were split, with some studies observing that phenotype A was associated with the highest incidence of GDM with up to 27.5% of patients [ 26 , 28 , 44 , 45 , 53 , 57 ]. In contrast, other studies found no significant difference [ 26 , 28 , 44 , 45 , 53 , 57 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological data recommend that PCOS causes a high prevalence of ovarian dysfunction and anovulation, where both of these conditions are positively correlated with a progressive chance of infertility [ 12 ]. Women with polycystic ovary syndrome appear to experience various conditions during pregnancy, including abortion, preterm delivery, and intrauterine death or stillbirth [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%